Foreign Direct Investment And Accounting Conservatism: IFRS Adoption As Moderating Variable - Siti Naziyatul Ulfa; Zaitul Zaitul; Herawati Herawati; Mardiana Azizah; Desi Ilona (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study examines the effect of moderation in IFRS adoption on the relationship between Foreign Direct Investment (FDI) and accounting conservatism. The object of research is companies listed on the Indonesia Stock Exchange (IDX) mining sector. Seventeen companies were the final samples, and three hypotheses were tested in this study. This study also uses control variables: company age, size, and profitability. Hypothesis testing uses Moderate Regression Analysis (MRA) SPSS version 16.0. The results of this study indicate that (i) Foreign Direct Investment (FDI) has a positive effect on accounting conservatism, (ii) The adoption of IFRS does not affect accounting conservatism, and (iii) the Adoption of IFRS cannot moderate the relationship of Foreign Direct Investment (FDI) and accounting conservatism. For the control variable, only the profitability variable has a negative effect on accounting conservatism.